Symmetrical peripheral gangrene associated with peripartum cardiomyopathy - Ajay Jaryal; Sujeet Raina; Surender Thakur; Tushar Sontakke (Wolters Kluwer Medknow Publications, 2013)
Symmetrical peripheral gangrene (SPG) is a rare clinical entity. It was first described in late 19 th century and since then has been reported with array of medical conditions mainly those complicated with shock, sepsis, and disseminated intravascular coagulation (DIC). Here in, we describe a parturient with peripartum cardiomyopathy (PPCM) and SPG. Clinicians should be aware of this entity as early recognition can help in reducing morbidity and mortality.